PRILAKU MAKAN EXTERNAL DAN RESTRAINED EATING BERHUBUNGAN DENGAN TOTAL PERSEN LEMAK PADA REMAJA - Akhriani, Mayesti; Nurhayati, Aftulesi; Billah, Muhammad Muayyad; Kurniawati, Meti; Muharammah, Alifiyanti (Ensiklopedia of Journal, 2025)
Abstract: Adolescent obesity is a nutritional problem in society influenced by genetic factors, excess energy intake and a sedentary lifestyle. Emotional eating, external eating and restraint are eating behaviors leading to excessive intake. This study aimed to determine the correlation between eating behavior (emotional, external and eating control) and the percentage of total fat in adolescents. This cross-sectional study recruited 79 teenagers aged 15-17 years, with a gender proportion of 75% female. Data collected in December 2022 includes eating behavior data using the Dutch Eating Behavior Questionnaire (DEBQ) questionnaire in Bahasa. Anthropometric data including body weight and total percent fat used Bioelectrical Impedance Analysis (BIA), while body height was measured using a stadiometer. The results of the nutritional status of Body Mass Index (BMI) to age showed that 27% of respondents were overweight with a median total fat percentage of 24%. The results of the Sperman-Rank statistical test showed that there was a significant relationship between external eating and total fat percentage (p value 0.015), and restrained eating and total fat percentage (p value 0.001). The conclusion of this study is that there is no significant correlation between emotional eating and total fat percentage, and there was a significant relationship of external and restrained eating with total fat percentage in adolescents.Keywords: External, Restrained, Adolescents